2015
DOI: 10.4049/jimmunol.1500283
|View full text |Cite
|
Sign up to set email alerts
|

Ctr2 Regulates Mast Cell Maturation by Affecting the Storage and Expression of Tryptase and Proteoglycans

Abstract: Copper (Cu) is essential for multiple cellular functions. Cellular uptake of Cu+ is carried out by the Ctr1 high affinity Cu transporter. The mobilization of endosomal Cu pools is regulated by a protein structurally similar to Ctr1, called Ctr2. It was recently shown that ablation of Ctr2 caused an increase in the concentration of Cu localized to endolysosomes. However, the biological significance of excess endolysosomal Cu accumulation has not been assessed. Here we addressed this issue by investigating the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…For this purpose we used the fast garnet assay, a method that detects trypsin-like activity. 14 However, the fast garnet method will detect a range of proteases with trypsin-like activity, that is, not just mast cell tryptase, and to evaluate to what extent mast cell tryptase accounts for the total trypsin-like activity in mast cells we therefore subjected both wild-type and tryptase-deficient (mMCP6 −/− ) mast cells to fast garnet staining. As seen in Figure 8 , wild-type mast cells stained strongly and the staining showed a distinct granular appearance, in agreement with the location of tryptase within the secretory granules.…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose we used the fast garnet assay, a method that detects trypsin-like activity. 14 However, the fast garnet method will detect a range of proteases with trypsin-like activity, that is, not just mast cell tryptase, and to evaluate to what extent mast cell tryptase accounts for the total trypsin-like activity in mast cells we therefore subjected both wild-type and tryptase-deficient (mMCP6 −/− ) mast cells to fast garnet staining. As seen in Figure 8 , wild-type mast cells stained strongly and the staining showed a distinct granular appearance, in agreement with the location of tryptase within the secretory granules.…”
Section: Resultsmentioning
confidence: 99%
“…bacteria and yeast) and there is also evidence supporting that copper can regulate neutrophil and macrophage function [16, 21]. As regards mast cells, it was shown in a previous study that mast cells lacking Ctr2, a protein implicated in copper transport, exhibited altered homeostasis [22]. However, the direct impact of copper on mast cells has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Yeast CTR2 has been shown to regulate internal pools of Cu under low Cu conditions 8, 9 , suggesting that the human homolog may have a similar Cu regulatory function. Recent studies found that CTR2 plays a role in mast cell maturation and hemostasis 10 , and that CTR1 protects CTR2 protein from degradation 11 .…”
Section: Introductionmentioning
confidence: 99%